Avaliação do equilíbrio postural em mulheres continentes e incontinentes - Nunes, Kelly Christina de Faria (2020)
Introduction: Urinary incontinence (UI) is defined as any involuntary loss of urine, which can be detected by abnormalities of the bladder, neurological diseases or changes in the strength of the pelvic muscles, in addition to increased pressure on the pelvic muscles (MAP), ligaments and connective tissue. Objective: To analyze and compare the postural balance of continent and incontinent women. Materials and methods: This is a cross-sectional study, with a quantitative approach. Thirteen women were included, divided into two groups: 6 incontinent women (group GI) and 7 continent women (group GC). The evaluation of postural balance was performed on the force platform and was tested in the following tasks: feet with eyes open (BI_OA), feet with eyes closed (BI_OF), standing on a foam of approximately 15 cm thick with eyes open (ESP_OA) and closed (ESP_OF) and with unipodal support with eyes open (UNI_OA). The following features were calculated: RMS of the displacement of the center of pressure (COP) in the mid-lateral (COP_X) and anteroposterior (COP_Y) directions, total displacement (DT) and total mean speed (VMT), characteristics of DFA (Detrended Fluctuation Analysis) and SDA (Stabilogram Diffusion Analysis). The data processing collected from the force platform was performed through routines programmed in the R software. Statistical analysis was performed after resampling the original data 20 times using the Bootstrap technique. Categorical variables were represented by frequency distribution and numerical measures by measures of central tendency and variability. The data were tested with the Shapiro-Wilk normality test, in the variables in which the hypothesis of the data was rejected, the Mann-Whitney test was used, for the data with normal distribution the t-student test was used. Value of α was fixed at 0.05 or 5% (p <0.05). For statistical analysis, the R software was used. Results: Six incontinent women with an average age of 41.5 ± 9.13 years participated in the study, and seven continent women with an average age of 35.29 ± 4.99 years (p = 0.32). In the analysis of the stabilometric variables, the continent women presented greater displacement with a significant difference from COP_Y in the following tasks BI_OA, ESP_OF, UNI_OA and the incontinent women presented a greater displacement, with significant difference only in the task BI_OF. When comparing DT and VMT between the two groups, it was noted that incontinent women had higher averages with a significant difference only in the BI_OF task, while for the continent women these values were in the ESP_OA, ESP_OF and UNI_OA tasks. When comparing the DFA between the two groups, it was found that both incontinent women and continent women showed persistent movement. Regarding the time in the mediolateral and anteroposterior directions (t_X and t_Y respectively) and, the amplitude in the mediolateral and anteroposterior directions (ampl_X and ampl_Y respectively), determined at the critical point calculated by the SDA, it was noted that incontinent women showed less time (t_X and t_Y) and less amplitude (ampl_X and ampl_Y) in the tasks of greater and lesser stability, BI_OA and UNI_OA, respectively. Conclusion: The studied variables suggest that the balance of incontinent women is negatively affected in the tasks with greater instability.